Communication between pre-hospital and intra-hospital emergency medical services: literature review - Melorie Marano de Souza; Allan Corrêa Xavier; Cássia Amorim Rodrigues Araújo; Eric Rosa Pereira; Sabrina da Costa Machado Duarte; Priscilla Valladares Broca
ABSTRACT Objectives: to analyze, according to the scientific literature, communication strategies in the transfer of cases between pre-hospital and in-hospital services and their contributions to patient safety. Methods: this is a literature review study, that is, one that aims to gather and synthesize research results on the subject in a systematic and orderly manner. Results: ten articles were published, published between 2010 and 2018, and two points of discussion emerged: use of mnemonics; and barriers to transferring a case. Conclusions: studies point to the need to standardize the case transfer process, as well as integrative training of professionals, regular assessment of the teams involved in emergency medical services and the need for research on the subject.